Biological determinants of blood‐based cytokines in the Alzheimer's disease clinical continuum. Issue 1 (22nd August 2022) - Galgani, Alessandro; Vergallo, Andrea; Campese, Nicole; Lombardo, Francesco; Pavese, Nicola; Petrozzi, Lucia; LoGerfo, Annalisa; Franzini, Maria; Cecchetti, Denise; Puglisi‐Allegra, Stefano; Busceti, Carla L.; Siciliano, Gabriele; et al.
Abstract: Converging translational and clinical research strongly indicates that altered immune and inflammatory homeostasis (neuroinflammation) plays a critical pathophysiological role in Alzheimer's disease (AD), across the clinical continuum . A dualistic role of neuroinflammation may account for a complex biological phenomenon, representing a potential pharmacological target. Emerging blood‐based pathophysiological biomarkers, such as cytokines (Cyt) and interleukins (ILs), have been studied as indicators of neuroinflammation in AD. However, inconsistent results have been reported probably due to a lack of standardization of assays with methodological and analytical differences. We used machine‐learning and a cross‐validation‐based statical workflow to explore and analyze the potential impact of key biological factors, such as age, sex, and apolipoprotein‐E (APOE) genotype (the major genetic risk factor for late‐onset AD) on Cyt. A set of Cyt was selected based on previous literature, and we investigated any potential association in a pooled cohort of cognitively healthy, mild cognitive impairment (MCI), and AD‐like dementia patients. We also performed explorative analyses to extrapolate preliminary clinical insights. We found a robust sex effect on IL12 and an APOE‐related difference in IL10, with the latter being also related to the presence of advanced cognitive decline. IL1β was the variable most significantly associated with MCI‐to‐dementia conversion over a 2.5 year‐clinical follow‐up. Although preliminary, our data support further clinical research to understand whether plasma Cyt may represent reliable and noninvasive tools serving the investigation of neuroimmune and inflammatory dynamics in AD and to foster biomarker‐guided pathway‐based therapeutic approaches, within the precision medicine development framework. Abstract : Blood cytokines are emerging as potential pathophysiological biomarkers in Alzheimer's Disease (AD). In this paper, it was explored in a population of cognitively healthy participant subjects and patients belonging to the Alzheimer's continuum, whether cytokine blood levels are influenced by biological factors, such as age, sex, and apolipoprotein‐E (APOE) genotypes and how they may be related to the clinical features of the patients. Machine‐learning network analysis shows that IL1β is significantly associated with MCI‐to‐dementia conversion. In parallel, it is demonstrated that sex and age influence interleukin IL12 concentration, while IL10 is related to the APOE genotype. Cytokine analysis may foster biomarker‐guided pathway‐based therapeutic approaches in AD.